A Review of Ground Heat Exchangers for Cooling Application in the Malaysian Climate - M. Y., Taib; Shahrani, Anuar; Hassan, Ibrahim (Penerbit UMP, 2015)
The ground heat exchanger (GHE) is one of the energy sources that has been identified since the 1970s which is able to produce sustainable energy for cooling which is in passive side. GHEs are widely implemented around the world, especially in European countries and a few Asian countries. In Malaysia, application of GHE is still considered as a new passive cooling approach in building energy reduction. Therefore, this paper reviews several important ways of implementing GHE in order to supply passive cooling for any application. The review covers general implementation of the GHE for thermal comfort and agricultural greenhouse cooling. The ground temperature variation used in different researches is also reviewed in this paper as an important part of identifying potential GHE implementations. Design and performance aspects of the GHE are also reviewed. Finally, this paper summarizes the potential and benefit of GHE implementation in the Malaysian climate for cooling applications to reduce the energy used in buildings and greenhouse gas emission.